2011
DOI: 10.1016/j.homp.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Use of homeopathic preparations in experimental studies with abiotically stressed plants

Abstract: Abiotically stressed plant models seem to be a useful approach to investigate homeopathic basic research questions, but more experimentation and especially more independent replication trials are needed. Systematic negative control experiments should be implemented on a routine basis to exclude false-positive results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
2
17
0
4
Order By: Relevance
“…a considerable increase of treatment effect when working with stressed seeds (Brizzi et al , 2011. This behavior was confirmed in a recent review regarding the use of homeopathic preparations in experimental studies with abiotically stressed plants (Jäger et al 2011), whereas in healthy plant tests the effects were less pronounced ). The first general conclusion we can make on the germination results reported here is that the As 45× treatment induced a marked stimulating effect, in terms of an overall reduction in the number of non-germinated seeds (−26.6%).…”
Section: Discussionsupporting
confidence: 56%
“…a considerable increase of treatment effect when working with stressed seeds (Brizzi et al , 2011. This behavior was confirmed in a recent review regarding the use of homeopathic preparations in experimental studies with abiotically stressed plants (Jäger et al 2011), whereas in healthy plant tests the effects were less pronounced ). The first general conclusion we can make on the germination results reported here is that the As 45× treatment induced a marked stimulating effect, in terms of an overall reduction in the number of non-germinated seeds (−26.6%).…”
Section: Discussionsupporting
confidence: 56%
“…The last reviews on plant-based test systems in homeopathic basic research were published in 2009/2011 in a series of three articles by Majewsky et al, 1 Betti et al 2 and Jäger et al 3 Majewsky et al 1 included unimpaired plants; Betti et al 2 and Jäger et al 3 included biotically and abiotically stressed plants as test systems, respectively, including publications since 1920. The two reviews dealing with unimpaired and biotically stressed plants included publications up to 2008, 1,2 and the other review included publications up to 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The two reviews dealing with unimpaired and biotically stressed plants included publications up to 2008, 1,2 and the other review included publications up to 2010. 3 The quality of publications was assessed using a pre-defined manuscript information score (MIS). Only publications scoring at least 5 out of 10 possible points were considered for further evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Since several experiments demonstrated that diseased plants normally have a more marked reaction to treatments at low or high dilution level than healthy ones [3], we decided to use an isopathic approach, as performed in other plant model systems [8,17]. According to isopathy, the same substance causing the disease can be used in low doses or high dilutions to treat the disease itself [18]: in our experimentation preliminary stressing of pollen grains with sub-lethal doses of arsenic trioxide was carried out in order to reduce germination rate, followed by treatments with the same substance at low and ultra-high dilutions.…”
Section: Introductionmentioning
confidence: 99%